Chemical composition and in sacco ruminal degradation of tropical trees rich in condensed tannins - Belachew, Z.; Yisehak, K.; Taye, T.; Janssens, G.P.J. (Czech Journal of Animal Science, 2013)
The study was aimed at determining the chemical composition, in sacco ruminal dry matter and organic matter degradability of leaves and fruits of tropical condensed tannin rich multipurpose tree species (MPTS). The MPTS studied were Ekebergia capenesis, Ficus sycomorus, Maesa lanceolata, and Rhus glutinosa. Chemical composition of dry matter (DM), crude protein (CP), crude ash (CA), ether extract (EE), crude fibre (CF), neutral detergent fibre (NDF), non-fibre carbohydrates (NFC), and condensed tannin (CT) was determined. In sacco rumen degradability was measured using three rumen fistulated Holstein Friesian-Boran cross steers at 0, 6, 12, 24, 48, 72, and 96 h. The DM and organic matter (OM) degradability data were fitted to the equation Y = a + b(1 - e-ct). The values for each chemical constituent ranged 5.43-11.49% (CA), 7.97-17.06% (CP), 1.57-31% (EE), 12.20-27.5% (CF), 5.84-39.30% (NFC), and 7.2-16.72% (CT). Ekebergia capensis leaves had the greatest values for slowly degradable fraction (b), effective degradability (ED), and rate of degradation (c) in DM (P < 0.001) whereas E. capensis fruit had significantly the greatest soluble fraction (a), potential degradability (b), and effective degradability (ED) values as compared to the a, PD, and ED values in the fruits of other plants(P < 0.001). Yet in OM degradation kinetics, the greatest and least values of potential degradability (PD) were recorded for F. sycomorus (89.89%) and E. capensis (55.90%) leaves (P < 0.001). Similar to the rapidly soluble fraction a, ED was found to be the greatest in fruits as compared to leaves of the plants (P < 0.001). Generally variation of plant parts led to significant differences in chemical composition, DM, and OM degradability and the degradable parameters. The leaves and fruits recorded more than 60% DM and OM degradability at 24 h, which implied that they were all greatly degradable in the rumen.
Keywords: dry matter and organic matter degradability; chemical composition; in sacco rumen degradation; fruit; leaf; multipurpose trees; tannins